PERIPHERAL UNITS OF PROPER NOUNS (WITH EXAMPLES OF FAMOUS PEOPLES’ NAMES IN ENGLISH AND UZBEK LANGUAGES) - X. B. Samigova; S. Sh. Khaydarova (Galaxy International Interdisciplinary Research Journal, 2021)
The article is devoted to the actual means of linguistic expressiveness - periphrases. The focus is on the final periphrases famous persons in modern media texts, and in biographical books; the peculiarities of their creation and use, taking into account linguistic and extralinguistic factors. Throughout the research, the position of peripheral units was studied and the sources were analyzed.